2010
DOI: 10.3354/meps08780
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lowered pH on marine phytoplankton growth rates

Abstract: Continued anthropogenic carbon emissions are expected to result in an increase in atmospheric CO 2 concentration to 700 ppm by the end of this century. This will cause a corresponding drop in the global average surface water pH of the oceans by ~0.4 units to ~7.8 and an increase in the CO 2 concentration of seawater. Ocean acidification may potentially both stimulate and reduce primary production by marine phytoplankton. Data are scarce on the response of marine phytoplankton growth rates to lowered pH/increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 64 publications
(80 reference statements)
6
67
2
Order By: Relevance
“…The delayed phytoplankton peak at 4000 µatm suggests that the immediate injection of CO 2 induced a temporary stress for phytoplankton growth; after a few days, however, growth returned to normal levels. Our findings are in accordance with other studies that found no significant changes in growth, taxonomic shifts, photosynthetic activity or total PON and POC of coastal phytoplankton communities within realistic future predicted OA scenarios (Berge et al 2010, Nielsen et al 2010. However, truly oceanic species and calcifying organisms might be sensitive to anthropogenic CO 2 changes (Müller et al 2010) as diel and seasonal CO 2 variability are generally lower in oligotrophic oceans compared to high productive coastal sites.…”
Section: Discussionsupporting
confidence: 92%
“…The delayed phytoplankton peak at 4000 µatm suggests that the immediate injection of CO 2 induced a temporary stress for phytoplankton growth; after a few days, however, growth returned to normal levels. Our findings are in accordance with other studies that found no significant changes in growth, taxonomic shifts, photosynthetic activity or total PON and POC of coastal phytoplankton communities within realistic future predicted OA scenarios (Berge et al 2010, Nielsen et al 2010. However, truly oceanic species and calcifying organisms might be sensitive to anthropogenic CO 2 changes (Müller et al 2010) as diel and seasonal CO 2 variability are generally lower in oligotrophic oceans compared to high productive coastal sites.…”
Section: Discussionsupporting
confidence: 92%
“…Culture experiments have revealed that many phytoplankton species grow well over a large range of pH (Hinga 2002, Berge et al 2010, Liu et al 2010, Joint et al 2011) especially when the pH change was caused by TA perturbations. However, truly oceanic species growing in situ are not exposed to large fluctuations in pH and may be more sensitive to such changes.…”
Section: Inorganic Carbon Speciation and Availabilitymentioning
confidence: 99%
“…Increased CO 2 enhanced rates of primary productivity (Wu et al, 2010;Trimborn et al, 2013) and growth (Sobrino et al, 2008;Tew et al, 2014;Baragi et al, 2015;Chen et al, 2015;King et al, 2015) in some diatom species, while others were unaffected (Chen and Durbin, 1994;Sobrino et al, 2008;Berge et al, 2010;Trimborn et al, 2013;Chen et al, 2015;Hoppe et al, 2015;King et al, 2015;Bi et al, 2017). In contrast, CO 2 -related declines in primary productivity and growth rate have also been observed (Barcelos e Ramos et al, 2014;Hoppe et al, 2015;King et al, 2015;Shi et al, 2017), suggesting that responses to ocean acidification are largely species specific.…”
mentioning
confidence: 99%